Odpowiedź:
Szczegółowe wyjaśnienie:
1) 4x + 8 = 2x - 12
4x - 2x = -12 - 8
2x = - 20/:2
x = -10
2) 20 - 4x = x - 5
-4x - x = - 5 - 20
-5x = -25/:(-5)
x = 5
3) -4x - 6 = 8x + 6
-4x - 8x = 6 + 6
-12x = 12/:(-12)
x = -1
4) x - 7 = 2x - 7
x - 2x = - 7 + 7
-x = 0/:(-1)
x = 0
5) 7 -3x = 1 + 2x
-3x -2x = 1 - 7
- 5x = -6/:(-5)
x = [tex]\frac{6}{5}[/tex] = [tex]1\frac{1}{5}[/tex]
6) -0,2 + 4x = 0,8 -2x
4x + 2x = 0,8 + 0,2
6x = 1/:6
x = [tex]\frac{1}{6}[/tex]
7) - 6 - 4x = 25 -2x
-4x + 2x = 25 + 6
-2x = 31/:(-2)
x = [tex]-\frac{31}{2}[/tex] = [tex]-15\frac{1}{2}[/tex]
8) 1,8x + 3 - 2,8x = x + 1
1,8x - 2,8x - x = 1 - 3
-2x = -2/:(-2)
x = 1
9) 6x + 6 - 5x = 2x + 7
6x - 5x - 2x = 7 - 6
-x = = 1/:(-1)
x = - 1
10) 3,5x + 3 = 2x + 7,5
3,5x - 2x = 7,5 - 3
1,5x = 4,5/:1,5
x = 3